Demand-led system approaches boost early generation seed production and enhance common bean seed and grain supply in Zambia - Mulube, Mwiinga; Lungu, Robert; Aseete, Paul; Kalemera, Sylvia; Cheyo, Esther; Nkhata, Wilson; Birachi, Eliud; Rubyogo, Jean Claude (2023)
This article describes the efforts and outcomes of increasing early generation seed (EGS) production and availability of quality seed of common bean varieties in Zambia, using a demand-led seed systems approach. The approach involved defining and ranking bean varieties based on market and farmer preferences, then investing in seed increase, catalyzing off-taker investment in grain off-taking and production, collaborative marketing campaigns, capacity building of seed producers, and strategic multi-stakeholder partnerships. The results showed that EGS production increased by 221.4%, and certified seed production increased six times from 2021 to 2023. Prioritized cultivars accounted for 88% of seed output, a path to desired variety turnover. The intervention was also associated with an increase in bean grain production of 10.2% in 2023, and bean harvest area by 11%. The demand-led system approach can improve seed availability and variety selection, and enhance common bean grain supply in Zambia, by linking EGS production with bean corridors and grain off-takers. Collaboration among stakeholders is crucial for its effective implementation and farmer training and support are essential for increased production.